The importance of reactive oxygen species on the aqueous phototransformation of sulfonamide antibiotics: kinetics, pathways, and comparisons with direct photolysis. (1st February 2019) - Ge, Linke; Zhang, Peng; Halsall, Crispin; Li, Yanying; Chen, Chang-Er; Li, Jun; Sun, Helin; Yao, Ziwei
Abstract: Sulfonamide antibiotics (SAs) are increasingly detected as aquatic contaminants and exist as different dissociated species depending on the pH of the water. Their removal in sunlit surface waters is governed by photochemical transformation. Here we report a detailed examination of the hydroxyl radical (OH) and singlet oxygen ( 1 O2 ) mediated photooxidation of nine SAs: sulfamethoxazole, sulfisoxazole, sulfamethizole, sulfathiazole, sulfamethazine, sulfamerazine, sulfadiazine, sulfachloropyridazine and sulfadimethoxine. Both OH and 1 O2 oxidation kinetics varied depending on the dominant protonated states of the SA in question (H2 SAs +, HSAs 0 and SAs − ) as a function of pH. Based on competition kinetic experiments and matrix deconvolution calculations, HSAs 0 or SAs − (pH ∼5–8) were observed to be more highly reactive towards OH, while SAs − (pH ∼8) react the fastest with 1 O2 for most of the SAs tested. Using the empirically derived rates of reaction for the speciated forms at different pHs, the environmental half-lives were determined using typical 1 O2 and OH concentrations observed in the environment. This approach suggests that photochemical 1 O2 oxidation contributes more than OH oxidation and direct photolysis to the overall phototransformation of SAs in sunlit waters. Based on the identification of key photointermediates using tandem mass spectrometry, 1 O2 oxidation generally occurred at the amino moiety on the molecule, whereas OH reaction experienced multi-site hydroxylation. Both these reactions preserve the basic parent structure of the compounds and raise concerns that the routes of phototransformation give rise to intermediates with similar antimicrobial potency as the parent SAs. We therefore recommend that these phototransformation pathways are included in risk assessments concerning the presence and fate of SAs in waste and surface waters. Graphical abstract: Image 1 Highlights: Aquatic photooxidation of sulfonamides (SAs) via reactive oxygen species is important. The kinetics depend on pH and separate reactivities of H2 SAs +, HSAs 0 and SAs − . 1 O2 plays a key role in aquatic fate of SAs compared with OH and direct photolysis Different primary pathways and multiple intermediates occur for the three reactions.